Automatic Fan With Ultrasonic Distance Sensor HC-Sr04 - Muhammad Nuhkenda AlFasyah Fasyah; Kemas Wahyu Hidayat; Dedy Haryanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
Increasingly sophisticated technology has a major impact on the creation of innovations in the development or creation of new electronic devices Fans are conventional electronic devices that are often used as air circulation regulators during hot weather. To overcome this problem, sensor technology can be used to detect the presence of humans and regulate the fan automatically. Using ultrasonic sensors, the fan can be set to turn on or off according to the distance or presence of people around it. A fan is considered a flexible air conditioner because it can be easily moved from one place to another. In this mode, the system works based on the ultrasonic distance sensor HC-SR04, the reading from the sensor is used as a parameter to turn the fan on or off using Adapters are devices that function to convert AC voltage to DC, meaning that alternating electric current (AC) voltage will be converted to unidirectional electric current voltage (DC). In principle the working principle of the adapter, it can be said to function as a power supply device.